(untitled) (PerCursos, 2023)
This article is part of more general issue of the relationship between nature and culture and its analysis subject is the relational binomial conflict and cooperation and their interfaces with the histories of ideas and social organization in Western societies. The purpose is to reflect on how different interaction forms established between humans throughout history have influenced the patterns of relationship between humans and nature. These, in turn, gave rise to the ways of life recognized by us today as those of pre-modern and modern societies. In order to demonstrate this statement, some central aspects of the scientific and philosophical thought evolution of both civilizations are compared, based on three general axes that define and distinguish them: 1) the cosmogonies and cosmologies; 2) the materialities engendered in the patterns of human-nature interactions; 3 the prevailing patterns of rationality. The final considerations bring some notes on contemporary human societies, suggesting that, in current times, despite the intensification of conflicts between nations and the revitalization of extreme right movements, or perhaps also because of this, there is a tendency towards equalization (greater symmetry) of the competition and cooperation principles within the fields of ideas, values and future civilizing projects, which puts us in a process of reorganization of action strategies to adapt to these inflections, generating results that are still unforeseen.